GAME EDUKASI RPG SEAL BREAKER MENGGUNAKAN RPG MAKER MV BERBASIS ANDROID - Sukanto, Petrus Sokibi; Adnyana, I Ketut Widhi (LPPM STMIK STIKOM Indonesia, 2018)
Finding insights into the questions for learning exercises is not only found in schools but outside the school environment such as reading books in the library or by utilizing the sophistication of Smartphones. The majority of children are very willing to play games, based on data from Appbrain (2015) shows that the number of games on Google Play are Action Games totaling 17,853, Casual Games 51,458, Puzzle Games 59,283, Game Education only 14,180. By playing an educational game, children can easily remember and discuss problems. The method used is a system approach with Object Oriented that uses AOO (Object Oriented Analysis) and DOO (Object Oriented Design) which are visualized with UML (Unified Modeling Language) and the results obtained from this study are games that are able to combine RPG games by discussing the questions of the junior high school national exams.